SuperMAP: Deep ultrafast MR relaxometry with joint spatiotemporal undersampling. Issue 1 (21st September 2022) - Li, Hongyu; Yang, Mingrui; Kim, Jee Hun; Zhang, Chaoyi; Liu, Ruiying; Huang, Peizhou; Liang, Dong; Zhang, Xiaoliang; Li, Xiaojuan; Ying, Leslie
Abstract : Purpose: To develop an ultrafast and robust MR parameter mapping network using deep learning. Theory and Methods: We design a deep learning framework called SuperMAP that directly converts a series of undersampled (both in k‐space and parameter‐space) parameter‐weighted images into several quantitative maps, bypassing the conventional exponential fitting procedure. We also present a novel technique to simultaneously reconstruct T1rho and T2 relaxation maps within a single scan. Full data were acquired and retrospectively undersampled for training and testing using traditional and state‐of‐the‐art techniques for comparison. Prospective data were also collected to evaluate the trained network. The performance of all methods is evaluated using the parameter qualification errors and other metrics in the segmented regions of interest. Results: SuperMAP achieved accurate T1rho and T2 mapping with high acceleration factors ( R = 24 and R = 32). It exploited both spatial and temporal information and yielded low error (normalized mean square error of 2.7% at R = 24 and 2.8% at R = 32) and high resemblance (structural similarity of 97% at R = 24 and 96% at R = 32) to the gold standard. The network trained with retrospectively undersampled data also works well for the prospective data (with a slightly lower acceleration factor). SuperMAP is also superior to conventional methods. Conclusion: Our results demonstrate the feasibility of generating superfast MR parameter maps through very few undersampled parameter‐weighted images. SuperMAP can simultaneously generate T1rho and T2 relaxation maps in a short scan time.